Review Essay: Changing Trends in Remembering Amundsen and Scott - Elzinga, Aant (Journal of Northern Studies, 2012)
Review of: Ross D. E. MacPhee, Race to the End. Amundsen, Scott, and the Attainment of the South Pole, New York: Sterling Publishing Co. 2010, ISBN 9781402770296, 245 pp. plus panorama foldout plates and map; Edward J. Larson, An Empire of Ice. Scott, Shackleton, and the Heroic Age of Antarctic Science, New Haven & London: Yale University Press 2011, ISBN 9780300154085, 288 pp.; Cornelia Lüdecke, Roald Amundsen. Ein biografisches Porträt, Freiburg–Basel–Wien: Verlag Herder GmbH 2011, ISBN 9783451062247, 208 pp.